Travesti envelhece, não vira purpurina! : um olhar interseccional sobre a(s) velhice(s) na experiência de travestis em Belo Horizonte - Lorena Hellen de Oliveira (2017)
This work aims to investigate the experiences of travestis, transgender people, regarding old age. It is about a field research realized in Belo Horizonte (MG), with five semi-structured interviews. From an intersectional perspective, it proposes to demonstrate how the combination of historical, social and political processes produced, among them, collective identifications and feelings of generational belonging, while it both seeks to explore the personal dimension of their experiences in this period. Considering that the articulation between different social markers acts not only in the categorization of subjects but also opens to them possibilities of agency, in this work emphasizes to how they are executed among the interlocutors, in their (re)appropriation and re-creation of the world(s), in micropolitics relations in their daily and in the capacity for them to resist, which make it possible not only to grow old, but age happily, despite all the social embarrassment they confront to survive.